2016
DOI: 10.1021/acs.inorgchem.6b00395
|View full text |Cite
|
Sign up to set email alerts
|

New Bifunctional Chelator p-SCN-PhPr-NE3TA for Copper-64: Synthesis, Peptidomimetic Conjugation, Radiolabeling, and Evaluation for PET Imaging

Abstract: Bifunctional chelators play an important role in developing metallic radionuclide-based radiopharmaceuticals. In this study, a new bifunctional ligand, p-SCN-PhPr-NE3TA, was synthesized and conjugated to a very late antigen-4 targeting peptidomimetic, LLP2A, for evaluating its application in 64Cu-based positron emission tomography (PET) imaging. The new ligand exhibited strong selective coordination of Cu(II), leading to a robust Cu complex, even in the presence of 10-fold Fe(III). The LLP2A conjugate of p-SCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(85 reference statements)
1
18
0
Order By: Relevance
“…Among the copper radioisotopes, 64 Cu (β + , t 1/2 = 12.7 h) appears to be a particular good candidate for positron emission tomography (PET) imaging owing to its relatively long decay and the possibility to form an interesting theranostic pair with the β – emitter 67 Cu isotope (β – , t 1/2 = 62 h). Among the numerous compounds used as chelators for 64 Cu labeling, 1,4,7‐triazacyclononane‐1,4,7‐triacetic acid (H 3 nota; Scheme ) has been the subject of intense research efforts, as it forms complexes with in vivo stabilities higher than those of 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid (H 4 dota) and 1,4,8,11‐tetraazacyclotetradecane‐1,4,8,11‐tetraacetic acid (H 4 teta) analogues . Commercially available nota derivatives have been developed owing to the interesting properties of this ligand scaffold for the envisaged applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the copper radioisotopes, 64 Cu (β + , t 1/2 = 12.7 h) appears to be a particular good candidate for positron emission tomography (PET) imaging owing to its relatively long decay and the possibility to form an interesting theranostic pair with the β – emitter 67 Cu isotope (β – , t 1/2 = 62 h). Among the numerous compounds used as chelators for 64 Cu labeling, 1,4,7‐triazacyclononane‐1,4,7‐triacetic acid (H 3 nota; Scheme ) has been the subject of intense research efforts, as it forms complexes with in vivo stabilities higher than those of 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid (H 4 dota) and 1,4,8,11‐tetraazacyclotetradecane‐1,4,8,11‐tetraacetic acid (H 4 teta) analogues . Commercially available nota derivatives have been developed owing to the interesting properties of this ligand scaffold for the envisaged applications.…”
Section: Introductionmentioning
confidence: 99%
“…By coupling p -SCN-PhPr-NE2P1A and p -SCN-PhPr-NE2A1P to LLP2A-PEG 4 via a thiourea bond formation, the corresponding products NE2A1P-PEG 4 -LLP2A and NE2P1A-PEG 4 -LLP2A were conveniently obtained in high yields. In addition, NOTA-PEG 4 -LLP2A and NE3TA-PEG 4 -LLP2A were also prepared 22 to compare their in vivo performances.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Gai et al designed a new probe 64 Cu-NE3TA-PEG4-LLP2A using the newly discovered chelator p-SCN-PhPr-NE3TA and assessed the diagnostic efficacy of the probe in melanoma xenografts. Small animal PET/CT imaging with 64 Cu-NE3TA-PEG4-LLP2A demonstrated high uptake with a superior tumor-to-muscle ratio at 4 h postinjection [173]. In addition, a study from Beaino et al reported that 177 Lu-DOTA-PEG 4 -LLP2A could accumulate not only in primary melanoma but also in the metastatic lesions in the lung and brain, demonstrating the potential of 177 Lu-DOTA-PEG 4 -LLP2A as an alternative treatment strategy for metastatic VLA-4 expressing melanoma [174].…”
Section: Other Pet/spect Probes For Melanoma Imagingmentioning
confidence: 99%